The Beltrami equations and lower Q-homeomorphisms - Kovtonyuk, D.A.; Petkov, I.V.; Ryazanov, V.I. (Труды Института прикладной математики и механики, 2010)
In this article it is shown that each homeomorphic W1,1loc solution to the Beltrami equation ∂f = μ∂f is the so-called lower Q-homeomorphism with Q(z) = Kμ(z) where Kμ(z) is dilatation quotient of this equation. It is developed on this base the theory of the boundary behavior and the removability of singularities of such solutions.